Kang Sheng Fitness Studio Management System - Tee, Lee Shi; Abdullah, Noryusliza (Applied Information Technology And Computer Science, 2025)
The Kang Sheng Fitness Studio Management System (KSFSMS) addresses critical challenges faced by fitness studios, exemplified by Kang Sheng Fitness. Manual processes for managing member data, class schedules, payments, and inventory result in inefficiencies, communication gaps, and errors. KSFSMS proposes an automated, centralized solution to streamline operations, improve communication, and offer data-driven insights. At Kang Sheng Fitness, KSFSMS will automate member registration, enhance class scheduling, streamline payments, and optimize inventory management. The objectives encompass designing a web-based fitness studio management system, tailoring it to specific needs, and testing its functionality. The system modules include Member Control, Class Scheduling and Booking, Instructor and Staff Management, Inventory Management, and Payment and Billing Management. Anticipated outcomes involve improved operational efficiency, enhanced member experiences, better staff coordination, and streamlined financial management. KSFSMS aims to transform Kang Sheng Fitness by offering a user-friendly platform, ensuring accurate data management, fostering member satisfaction, and enhancing overall profitability. This project holds significance in enhancing member experiences, operational efficiency, and financial stability, setting a new standard for fitness studio management. The subsequent chapters of the report delve into the literature review, chosen methodology, system analysis, and design, implementation, testing, conclusions, and recommendations for further insights and system development.